Possible Cognitive Benefits of Acute Physical Exercise in Children With ADHD: A Systematic Review. (March 2017) - Grassmann, Viviane; Alves, Marcus Vinicius; Santos-Galduróz, Ruth Ferreira; Galduróz, José Carlos Fernandes
Objective: Studies have suggested that even a single session of physical exercise enhances executive functions. ADHD is among the most common developmental disorders in childhood, but little is known about alternative treatments for this disorder. Therefore, we performed a systematic review of the literature to analyze articles that evaluated the executive functions of children with ADHD after an acute exercise session.Method: We reviewed articles indexed in the PubMed, American Psychiatric Association (APA) psychNET, Scopus, and Web of Knowledge databases between 1980 and 2013.Results: Of 231 articles selected, only three met the inclusion criteria.Conclusion: Based on these 3 articles, we concluded that 30 min of physical exercise reportedly improved the executive functions of children with ADHD. Due to the small number of articles selected, further studies are needed to confirm these benefits.